Selection and isolation defne a heterogeneous divergence landscape between hybridizing Heliconius butterfies - Van Belleghem, Steven M. (2021)
Hybridizing species provide a powerful system to identify the processes that shape genomic variation and maintain species bound- aries. However, complex histories of isolation, gene fow, and selection often generate heterogeneous genomic landscapes of di- vergence that complicate reconstruction of the speciation history. Here, we explore patterns of divergence to reconstruct recent speciation in the erato clade of Heliconius butterfies. We focus on the genomic landscape of divergence across three contact zones of the species H. erato and H. himera. We show that these hybridizing species have an intermediate level of divergence in the erato clade, which fts with their incomplete levels of reproductive isolation. Using demographic modeling and the relationship between admixture and divergence with recombination rate variation, we reconstruct histories of gene fow, selection, and demo- graphic change that explain the observed patterns of genomic divergence. We fnd that periods of isolation and selection within populations, followed by secondary contact with asymmetrical gene fow are key factors in shaping the heterogeneous genomic landscapes. Collectively, these results highlight the effectiveness of demographic modeling and recombination rate estimates to disentangling the distinct contributions of gene fow and selection to patterns of genomic divergence.